2009
DOI: 10.1080/08927010802592917
|View full text |Cite
|
Sign up to set email alerts
|

Development of the primary bacterial microfouling layer on antifouling and fouling release coatings in temperate and tropical environments in Eastern Australia

Abstract: The role played by bacteria during the pioneering stages of colonisation on marine coatings was investigated over three distinct seasons in both tropical and temperate environments. Novel methods were developed to facilitate the study of the adhered bacterial population on the test coatings in their native, hydrated state. The approach eliminated destructive sample preparation techniques, including sample dehydration and/or removal from the substratum surface prior to analysis. Bacterial colonisation during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 38 publications
1
44
0
1
Order By: Relevance
“…It has been shown that pennate diatoms dominate diatom communities in biofi lms (PATIL and ANIL 2005, and included citations) with frequently identifi ed pennate genera Navicula, Nitzschia, Cocconeis, Amphora (RAILKIN 2004), as was recorded in this study. The majority of studies showed the dominance of pennate genera Amphora, Navicula, Nitzchia (KHATOON et al 2007) and Cylindrotheca (MOLINO et al 2009;DOBRETSOV and THOMASON 2011;BRIAND et al 2012) on different artifi cial substrates as well as on fouling release coated substrates (CASSÉ and SWAIN 2006;ZARGIEL et al 2011). The recorded genera of diatoms in this study are therefore typical periphytic diatoms in biofi lms.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that pennate diatoms dominate diatom communities in biofi lms (PATIL and ANIL 2005, and included citations) with frequently identifi ed pennate genera Navicula, Nitzschia, Cocconeis, Amphora (RAILKIN 2004), as was recorded in this study. The majority of studies showed the dominance of pennate genera Amphora, Navicula, Nitzchia (KHATOON et al 2007) and Cylindrotheca (MOLINO et al 2009;DOBRETSOV and THOMASON 2011;BRIAND et al 2012) on different artifi cial substrates as well as on fouling release coated substrates (CASSÉ and SWAIN 2006;ZARGIEL et al 2011). The recorded genera of diatoms in this study are therefore typical periphytic diatoms in biofi lms.…”
Section: Discussionmentioning
confidence: 86%
“…Some of these effects have also been reported in field observations 16 . However, colonization models are mostly based on studies of natural substrata, such as wood and stone or traditional AF coatings that rapidly foul, and there are only a few reports that study the colonization of modern, non-biocidal AF coatings by microorganisms 19,20 . Fouling by biofilms composed of communities of bacteria, diatoms, fungi and protozoa has been largely ignored until recently, because the focus of research has been on macrofouling.…”
Section: Fouling Organisms and Their Settlement And Adhesion Strategiesmentioning
confidence: 99%
“…To predict the actual total number of bacteria under the cover slip, Equation 1 was used for each statistical measure, Total number of bacteria = statistical measure × 13,924 (…”
Section: Assessing the Accuracy And Reliability Of The Estimated Statmentioning
confidence: 99%
“…Previous studies on marine biofilms developing on surfaces submerged in the sea reported the use of scalpels to remove the biofilm from the substratum prior to enumeration on membrane filters [8][9][10][11][12]. Few studies reported the use of microscope slides to develop a biofilm and consequently enumerate bacteria in their native, hydrated conditions [6,13,14]. The originally developed method [15] involved the counting of the number of bacterial cells on the glass slide or using a filter within several squares of an ocular graticule or the use of a Whipping grid at 1000× magnification [4].…”
Section: Introductionmentioning
confidence: 99%